2002
DOI: 10.1002/jcb.10059
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol suppresses proliferation of cultured human colon and liver cancer cells by inhibiting DNA synthesis and activating apoptosis

Abstract: Magnolol, a hydroxylated biphenyl compound isolated from the Chinese herb Hou p'u of Magnolia officinalis, has been reported to have anti-cancer activity. In the present study, magnolol at very low concentrations of 3-10 microM inhibited DNA synthesis and decreased cell number in cultured human cancer cells (COLO-205 and Hep-G2) in a dose-dependent manner, but not in human untransformed cells such as keratinocytes, fibroblasts, and human umbilical vein endothelial cells (HUVEC). Magnolol was not cytotoxic at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 35 publications
3
49
0
Order By: Relevance
“…Many researchers have shown the various anticancer activities of magnolol. For example, magnolol suppresses proliferation of cultured human colon cancer cells by inhibiting DNA synthesis 21) ; magnolol-induced apoptotic death is mediated by blocking the EGFR-PI3K-Akt pathway and subsequent activation of the Bad-Bax-cytochrome c-caspase pathway in human prostate cancer cells 18) ; magnolol decreases cell number in a cultured human glioblastoma (U373) cancer cell line 20) ; magnolol (100 ”M) induces apoptosis in cultured human hepatoma (Hep G2) and colon cancer (COLO 205) cell lines. 26) More recently, magnolol-induced apoptosis in human gastric adenocarcinoma (SGC-7901) cells by mitochondrial and PI3K-Akt signaling pathways, 27) and magnolol has anticarcinogenic effects against UVB-induced skin tumor development in SKH-1 mice and a possible role in apoptosis during skin tumor development has been determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have shown the various anticancer activities of magnolol. For example, magnolol suppresses proliferation of cultured human colon cancer cells by inhibiting DNA synthesis 21) ; magnolol-induced apoptotic death is mediated by blocking the EGFR-PI3K-Akt pathway and subsequent activation of the Bad-Bax-cytochrome c-caspase pathway in human prostate cancer cells 18) ; magnolol decreases cell number in a cultured human glioblastoma (U373) cancer cell line 20) ; magnolol (100 ”M) induces apoptosis in cultured human hepatoma (Hep G2) and colon cancer (COLO 205) cell lines. 26) More recently, magnolol-induced apoptosis in human gastric adenocarcinoma (SGC-7901) cells by mitochondrial and PI3K-Akt signaling pathways, 27) and magnolol has anticarcinogenic effects against UVB-induced skin tumor development in SKH-1 mice and a possible role in apoptosis during skin tumor development has been determined.…”
Section: Discussionmentioning
confidence: 99%
“…18) Attention has been paid to its anticancer activity in several cancer cell lines, including colon cancer, hepatoma, leukemia, fibrosarcoma, melanoma, squamous carcinoma, and thyroid carcinoma. 18,19) Several researchers have shown that magnolol inhibits proliferation and induces apoptosis in cancer cells by upregulating p21 cip/Waf1 , 20) inhibiting DNA synthesis, 21) activating the epidermal growth factor receptor (EGFR)/phosphoinositide 3-kinase (PI3K)/Akt signaling pathway, 18) as well as Ras/Raf-1/ Erk actions. 22) However, it remains to be determined whether Note * To whom correspondence should be addressed.…”
mentioning
confidence: 99%
“…These anti-angiogenesis effects are attributed to HNK-induced suppression of vascular endothelial growth factor receptor R2 (KDR) phosphorylation, thus leading to inhibition of the mitogen-activated protein kinase (MAPK) and the phosphatidylinositol 3-kinase (PI3-kinase) pathways (19). Additional recognized activities of HNK include cytochrome C release and increased cytosolic free calcium (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…These findings demonstrate that AMPK mediates the anticancer effects of magnolol through apoptosis in HCT-116 cells. Several researchers have shown that magnolol inhibits proliferation and induces apoptosis in cancer cells by inhibiting DNA synthesis [25], signaling pathway as well as Ras/Raf-1/Erk actions [26]. However, it remains to be determined whether apoptotic cell death is associated with the AMPK signaling pathway in HCT-116 colon cancer cells treated with magnolol.…”
Section: Fadilah Et Almentioning
confidence: 99%